Historical changes of the statistical techniques and the methodologies for the study of the causality in medical sciences - Nelsa María Sagaró Del Campo; Larisa Zamora Matamoros (Centro Provincial de Información de Ciencias Médicas, 2019)
The statistical techniques constitute the mathematical tools that allow the causal analysis of the health problems; that is why it is import to know about their development through time, reason why the objective of this work was to elaborate a synthesis of the historical course of the techniques and methodologies used in the medical investigation in connection with the causality models that have prevailed in each historical moment. To such effects, a wide documental review was carried out and, for a better understanding, the changes were divided in five stages, according to the development reached in the statistical techniques. Also, the main facts and the fundamental characteristics of each stage are described and the binary logistical regression is highlighted as the most used technique.